Integration of sirah and geography elements in teaching and learning using multimedia approach / Erna Nurfazana Nurizan - Nurizan, Erna Nurfazana (2021)
Multimedia is one of a new approach to enhance teaching and learning method compare to the conventional teaching method that is face to face method. Teaching and learning in Sirah encounter difficulties in understanding the flow of Sirah, how to relate it to one another and to memorize the important event connected to Sirah subject. Sirah education is related to geography as most of Sirah subtopic connected to spatial information such as locations, direction, distance, area, and journey. This information can be enhanced by integrating three elements; Sirah, Geography and Multimedia through storytelling video in an application. This study emphasizes on the teacher, parents, and student perception on teaching and learning of Sirah subject with/without geography elements and constructing an application prototype with a storytelling video of the Sirah subject which cover year 5 subtopic of Islamic education syllabus. The data acquisition conducted through interview and questionnaire distribution to get the teacher, parent and students’ perception. Interview was conducted through phone-based method with a teacher and questionnaire distributed using two methods; fieldwork (hardcopy) and online (softcopy). The sample size for questionnaire were 148 respondents and the feedback on the integration of multimedia approach in teaching and learning being recorded. In addition, after designing storyboard and the graphical user interface, a prototype of storytelling applications constructed based on the storyboard created to achieve the integration of the elements. This prototype will be design based on geography elements (eg: location, direction and journey) which integrated with Sirah using multimedia platform.